Strategy for Leadership: How Principals of Successful Schools Improve Education Quality - Ismaya, Bambang; Sutrisno, Sutrisno; Darmawan, Didit; Jahroni, Jahroni; Kholis, Nur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to find out the extent of the principal's leadership strategy that has been carried out in improving the quality of education in Karawang. This type of research is descriptive qualitative research. The data collection tools used are interviews, observations and literature reviews. The object of the study was the principal of SMK 1 Karawang. The study was conducted from March to December 2016. The data analysis technique is a descriptive qualitative analysis technique consisting of data collection, data reduction, data presentation, and conclusion. The results of the study stated that there were several activities of the principal to implement the functions of the principal as a strategy for improving the quality of education at SMKN 1 Karawang. These functions include the educator function, the manager function, the administrator function, the supervisory function, the leader function, the innovator function, and the motivator function.